PERANCANGAN MEDIA PROMOSI DIVA SNACK FROZEN FOOD SEBAGAI UPAYA MENINGKATKANBRAND AWARENESS - Yunitasari, Fani Ismawati; Bahruddin, Muh; Dewanto, Thomas Hanandry (Jurnal ArtNouveau, 2014)
Heightened daily routine, requires every person to obtain practical food cooked and ready to eat. Diva product is a product that offers practicality in meeting food needs, backed up with so many variations of products made, good quality products and affordable prices. But not many people know about this Diva products, therefore the purpose of this design is how the Media Campaign Designing Diva Snack Frozen Food In Effort to Improve Brand Awareness. The design is done with a qualitative approach, through interview, observation and documentation to formulate design concepts. From the analysis, it was found that the absence of efforts to promote through the media, becoming one of the obstacles that make the product less recognizable Diva wider community. After going through the process of data analysis, it was found keywords or concepts design "Quick and Easy " which means fast and easy. In this " Quick and Easy" means how reliable Diva products for quick and easy presentation, to overcome hunger anytime. Resulting design is made by having the same unique on any media to become one entity own minds and get points prospective customers. Results are expected to improve the design of the public aware of the Diva product.